On Shifting Ground : Muslim Women in the Global Era - Nouraie-Simone, Fereshteh (Book collections on Project MUSE., 2014)
In Iran, hundreds of women are producing blogs, sharing their ideas in an Islamic republic that still limits women's expression. In Malaysia, members of Sisters in Islam are challenging sexist interpretations of Islamic theology and law. And throughout the Arabic-speaking world, satellite TV stations like Al-Jazeera have spawned 'new Scheherazades' - women journalists and hosts whose voices have a powerful impact on the public discourse. This unique, cutting-edge book of essays explodes Western stereotypes about Middle Eastern women.